Labour and Management Adjustments to a Changing International Economic Environment - Waisglass, Harry (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1974)
In this paper the author delivers some thoughts on the international setting in which Canada is striving to achieve its social and economic goals.